SIMULATION MODEL BASED ON REGIONAL DEVELOPMENT AND VIRTUAL CHANGES - Dlask, Petr (Acta Polytechnica, 2015)
This paper reports on change as an indicator that can be provide more focused goals in studies of development. The paper offers an answer to the question: How might management gain information from a simulation model and thus influence reality through pragmatic changes. We focus on where and when to influence, manage, and control basic technical-economic proposals. These proposals are mostly formed as simulation models. Unfortunately, however, they do not always provide an explanation of formation changes. A wide variety of simulation tools have become available, e.g. Simulink, Wolfram SystemModeler, VisSim, SystemBuild, STELLA, Adams, SIMSCRIPT, COMSOL Multiphysics, etc. However, there is only limited support for the construction of simulation models of a technical-economic nature. Mathematics has developed the concept of differentiation. Economics has developed the concept of marginality. Technical-economic design has yet to develop an equivalent methodology. This paper discusses an,alternative approach that uses the phenomenon of change, and provides a way from professional knowledge, which can be seen as a purer kind of information, to a more dynamic computing model (a simulation model that interprets changes as method). The validation of changes, as a result for use in managerial decision making, and condition for managerial decision making, can thus be improved.